Pengaruh sanitasi lingkungan dan perilaku keluarga terhadap kejadian penyakit demam berdarah dengue (DBD) di Kecamatan Benai Kabupaten Kuantan Singingi - Retno Wulandari; Rasoel Hamidy; Bayhakki Bayhakki (Pelantar Press, 2021)
Dengue hemorrhagic fever is an infection caused by the dengue virus, the dengue virus is transmitted through the bite of the Aedes aegypti mosquito. The incidence of dengue hemorrhagic fever is influenced by various factors such as environmental sanitation, economy and behavior. This study aims to determine the effect of environmental sanitation and family behavior on the incidence of dengue hemorrhagic fever in Benai District, Kuantan Singingi Regency. This type of research is quantitative with cross sectional design. Data analysis used univariate, bivariate with chi square test and multivariate using binary logistic regression model parameter testing. The results showed that the variables of environmental sanitation and behavior in Benai District, Kuantan Singingi Regency were not optimal so that they were at risk of experiencing dengue fever. Environmental sanitation and behavior variables simultaneously and significantly influence the incidence of dengue hemorrhagic fever in Benai District, Kuantan Singingi Regency. This is related to the large amount of waste that is not properly managed around residents' homes and there are also clean water storage places that are not closed, this condition is due to the lack of public knowledge about the importance of maintaining environmental cleanliness and how to do 3M. Besides that, the attitude of the people who do not care about it also illustrates that the behavior of the people in the area is still lacking.